Síntese e processamento de materiais cerâmicos avançados para aplicação em baterias de íons Li: otimização na obtenção de eletrólitos sólidos a base de Li₇La₃Zr₂O₁₂ - Janes, Danilo Biazon (2023)
The growth in demand for electronic devices and electric vehicles, seeking to use renewable energy sources, has accelerated the technological development in this segment. One of the constant needs for improvement is the efficiency of battery systems for energy storage. Given the varieties of batteries developed and improved, Li₇La₃Zr₂O₁₂ (LLZO) solid-state lithium-ion batteries have shown to be one of the most promising for having high ionic conductivity and good electrochemical stability. Due to the great interest in this material, studies have been directed to understand the challenges in the manufacture of LLZO seeking to achieve such properties. A large part of the LLZO's performance is given by the crystallographic configuration and morphology, which are controlled in the synthesis and processing. From powder preparation, through forming process to the sintering stage, many parameters are established and can impact both the quality of the product obtained, as well as the time and cost of production. Therefore, the objective of this work is to analyze the variables of the production process of solid electrolytes based on LLZO and to present an optimization of its synthesis and processing.